BERBAGI KEBAHAGIAAN BERSAMA LANSIA: MEMBANGUN KETERLIBATAN SOSIAL DAN KESEJAHTERAAN MELALUI KEGIATAN POSITIF - Aulia, Sisca; Natasha, Angelie Alice; Bernadett, Fiona CH; Junita Sari; Tanoto, Olivia; Cahyani, Regita Emelia (Jurnal Serina Abdimas, 2024)
The aging process is a natural stage in human life which is accompanied by physical, cognitive and social changes. In this context, the elderly are a population that requires special attention to ensure optimal quality of life. The social aspect of this activity includes exploring social support networks and participation in community activities. Detailed analysis of how social relationships influence the well-being of older adults is an important element in understanding the social impact of the aging process. An elderly home or nursing home is a place of care that is built specifically to provide housing, care and support to elderly people who need more attention for various reasons, such as declining physical or mental health, dependence on care, or lack of adequate family support. “Berbagi Kebahagiaan Bersama Lansia: Membangun Keterlibatan Sosial dan Kesejahteraan Melalui Kegiatan Positif” aims to create a creative activity space where the elderly can participate in various artistic and social activities. The methods used are observation, interviews, implementation methods include observing the implementation location, discussions with the administrators of elderly homes, carrying out BERKREASI activities by doing gymnastics and singing together. The program covers key aspects of creative programming, including event design, senior participation and health impacts. The results of the BERKREASI activity include making the elderly move healthily through exercise, increasing the enthusiasm and joy of the elderly through games with prizes and entertaining the elderly through singing together.